2004
DOI: 10.1111/j.1460-9568.2004.03796.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutant huntingtin affects the rate of transcription of striatum‐specific isoforms of phosphodiesterase 10A

Abstract: Huntington's disease (HD) is caused by the inheritance of a copy of the gene encoding mutant huntingtin with an expanded CAG repeat. Phosphodiesterase 10A (PDE10A) mRNA decreases in transgenic HD mice expressing exon 1 of the human huntingtin gene (HD). The mouse PDE10A mRNA is expressed through alternative splicing and polyadenylation in a tissue-specific manner and that transcription of striatal PDE10A mRNA is driven by two promoters. PDE10A2 is the predominant isoform of the gene is expressed in the striatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 49 publications
0
52
0
Order By: Relevance
“…PDE10A2 is a PDE10A splice variant (Hu et al, 2004), which is selectively expressed in striatal MSNs in the mouse brain (Sano et al, 2006(Sano et al, , 2007. Therefore, by knocking in tTA into the PDE10A2 gene locus, selective distribution of tTA in striatal MSNs was achieved in a manner that recapitulates expression of PDE10A2 (Sano et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…PDE10A2 is a PDE10A splice variant (Hu et al, 2004), which is selectively expressed in striatal MSNs in the mouse brain (Sano et al, 2006(Sano et al, , 2007. Therefore, by knocking in tTA into the PDE10A2 gene locus, selective distribution of tTA in striatal MSNs was achieved in a manner that recapitulates expression of PDE10A2 (Sano et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is some indirect evidence that PDE10A may be involved in long-term potentiation in the hippocampus as the level of its mRNA has been reported to be elevated after long-term potentiation (O'Connor et al, 2004). PDE10A mRNA and protein levels are decreased in the striatal region of brains from Huntington's diseased transgenic mice and the decrease precedes the onset of symptoms Hu et al, 2004). Thus, it is postulated that loss of PDE10 may cause an alteration in cyclic nucleotide signaling that contributes to the loss of neuronal function produced by the disease.…”
Section: Pharmacology/functionmentioning
confidence: 99%
“…However, the loss of striatally enriched transcripts early in disease or R6/2 model progression could be a consequence of transcriptional dysfunction caused by a direct interaction of soluble huntingtin protein with transcription factors required to direct expression of particular mRNAs or compensation for dysfunctional neuronal signaling. Studies of the regulation of the PDE10A promoter have not revealed any candidate regulatory transcription factors capable of decreasing PDE10A mRNA as observed in the R6/R2 mouse model (Hu et al, 2004). Given that inhibition of PDE10A is a powerful inducer of CREB-mediated transcription in striatum, and the propensity of this circuit to compensate for chronic deficits in signaling cascades, it seems possible that down-regulation of PDE10A early in the disease process may be an adaptive response to compensate for loss of cAMP signaling.…”
Section: Pde10 Suppression Affects Transmitter and Signaling Genes 73mentioning
confidence: 99%
“…Transcripts for PDE10A and PDE1B are abundant in striatum, but exhibit significant down-regulation in HD brain and the R6/2 mouse model. The decrease in PDE10A mRNA is caused by decreases in transcriptional initiation of the striatally expressed PDE10A2 gene, which initiates at sites 2 and 3 in the exon 1a-specific promoter (Hu et al, 2004), and loss of the PDE10A enzyme early in disease has been proposed as a contributing factor in progression of disease . However, the loss of striatally enriched transcripts early in disease or R6/2 model progression could be a consequence of transcriptional dysfunction caused by a direct interaction of soluble huntingtin protein with transcription factors required to direct expression of particular mRNAs or compensation for dysfunctional neuronal signaling.…”
Section: Pde10 Suppression Affects Transmitter and Signaling Genes 73mentioning
confidence: 99%